Introduction to Business - Gitman, Lawrence J.; McDaniel, Carl; Shah, Amit; Reece, Monique; Koffel, Linda; Talsma, Bethann; Hyatt, James C. (Open textbook library., 2018)
Introduction to Business covers the scope and sequence of most introductory business courses. The book provides detailed explanations in the context of core themes such as customer satisfaction, ethics, entrepreneurship, global business, and managing change. Introduction to Business includes hundreds of current business examples from a range of industries and geographic locations, which feature a variety of individuals. The outcome is a balanced approach to the theory and application of business concepts, with attention to the knowledge and skills necessary for student success in this course and beyond.